2002
DOI: 10.1002/joc.768
|View full text |Cite
|
Sign up to set email alerts
|

Solar correlates of Southern Hemisphere mid‐latitude climate variability

Abstract: Atmospheric circulation in the southern mid-latitudes is dominated by strong circum-Antarctic zonal west winds (ZWW) over the latitude range of 35 to 60°S. These winds exhibit coherent seasonal and interannual variability, which has been related both to Antarctic (e.g. polar ice) and low-latitude climate (e.g. El Niño-southern oscillation) parameters. Historical and recent studies suggest that, at its northern margins, variability in the ZWW also has a marked quasi-decadal component. Analysis of sea-level pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 36 publications
(55 reference statements)
6
58
0
Order By: Relevance
“…Thresher (2002Thresher ( , 2003 The most recent calculation of an L index has been by Thresher (2002Thresher ( , 2003. The L index time series shown in Thresher (2003) is indicated as being derived from a mixture of the Das and Pittock indices up to 1977, and one calculated by Thresher from 'daily Australian Bureau of Meteorology (BoM) charts' from 1967 to the present.…”
Section: Nccmentioning
confidence: 99%
See 2 more Smart Citations
“…Thresher (2002Thresher ( , 2003 The most recent calculation of an L index has been by Thresher (2002Thresher ( , 2003. The L index time series shown in Thresher (2003) is indicated as being derived from a mixture of the Das and Pittock indices up to 1977, and one calculated by Thresher from 'daily Australian Bureau of Meteorology (BoM) charts' from 1967 to the present.…”
Section: Nccmentioning
confidence: 99%
“…Here, the variation of the latitude of the subtropical ridge over eastern Australian longitudes (approximately 150°E) is examined and compared with conclusions reported by Thresher (2002Thresher ( , 2003. Connections between this index and the large-scale hemispheric circulation as manifested by the annular mode or Gibson's (1992) latitude of the subtropical wind maximum will be examined in a later study.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The fit between summer (January-March) mean sea surface temperatures (SSTs) at Maria Island and a pooled growth rate time series for the three shallow-water species is good, capturing both the long-term trends and a suggestion of quasi-decadal oscillations in both data sets (see ref. 19) (Fig. 2a).…”
mentioning
confidence: 98%
“…Pittock [16] has shown that the interannual variability of the latitude of the surface subtropical high pressure maximum over Eastern Australia is major mechanism influencing inter-annual rainfall variability. It has also been shown to be connected to the inter-annular variability of the annual mean maximum temperatures (Coughlan [17]), zonal westerly winds (Thresher [18]), meridional wind and mean air temperature, and ozone (Pittock [19]). …”
Section: Datamentioning
confidence: 99%